Impact of Pediatric Hematopoietic Stem-Cell Transplantation on Craniofacial Growth - Frascino, Alexandre Viana; Fava, Marcelo [UNESP]; Collassanti, Maria Dulce Silveira; Odone-Filho, Vicente (Elsevier, 2020)
OBJECTIVES: To assess the craniofacial skeletal growth in pediatric hematopoietic stem-cell transplantation (HSCT) survivors in comparison with age-sex matched-paired controls. METHODS: A case-controlled retrospective comparison of the craniofacial growth in 25 HSCT children and 25 matched-paired controls was conducted. Craniofacial growth was quantitatively assessed by linear and angular measurements in panoramic radiographic images using ImageJ¯. Stature growth and body weight were obtained through physical examination. Cancer diagnosis, myeloablative conditioning, and HSCT were retrieved from medical records. RESULTS: Patients aged 12.2 years (±3.8; 16 male, 9 female). Radiographic images were obtained on an average of 2.43 (±2.0) years after HSCT. The main malignant diagnosis was acute lymphoblastic leukemia (56%), followed by acute myeloid leukemia (36%) and myelodysplastic syndromes (8%). Total body irradiation was associated with chemotherapy at 80%. Mean age at transplantation was 10 (±4.7) years. HSCT survivors showed reduced a vertical growth of the mandibular ramus (p=0.003). This persisted among individuals below 12 years of age (p=0.017). The HSCT group showed delayed dental eruption, though there was no statistically significant difference (p=0.3668). The HSCT group showed stature deficit, increased weight, and body mass index (Z-score stature: -0.28; Z-score weight: 0.38, respectively). CONCLUSIONS: Pediatric HSCT has decreased vertical craniofacial growth compared to their matched controls. There might be an association between reduced craniofacial vertical growth and reduced estature growth. Further studies to quantitatively investigate the impact of different myeloablative regimens in craniofacial skeletal growth and development.